MỤC LỤC
Cho hàm số f(x) có đạo hàm liên tục trên $\Large\mathrm{ (0 ;+\infty)}$, biết $\Large\mathrm{f^{\prime}(x)+(2 x+4) f^{2}(x)=0}$ và $\Large\mathrm{f(x)>0, \forall x \in \mathbb{R} ; f(2)=\dfrac{1}{15}}$. Tính f(1)+f(2)+f(3)
Lời giải chi tiết:
Biến đổi: $\Large\mathrm{f^{\prime}(x)+(2 x+4) f^{2}(x)=0 \Leftrightarrow \dfrac{f^{\prime}(x)}{f^{2}(x)}=-2 x-4 \Rightarrow \int \dfrac{f^{\prime}(x)}{f^{2}(x)} d x=\int(-2 x-4) d x}$
$\Large\mathrm{\Leftrightarrow \int \dfrac{d f(x)}{f^{2}(x)}=-x^{2}-4 x+C \Leftrightarrow-\dfrac{1}{f(x)}=-x^{2}-4 x+C \Rightarrow f(x)=\dfrac{1}{x^{2}+4 x-C}}$
Với $\Large\mathrm{f(2)=\dfrac{1}{15} \Rightarrow \dfrac{1}{15}=\dfrac{1}{12-C} \Rightarrow C=-3,}$ suy ra: $\Large\mathrm{f(x)=\dfrac{1}{x^{2}+4 x+3}}$
Khi đó: $\Large\mathrm{f(1)+f(2)+f(3)=\dfrac{1}{8}+\dfrac{1}{15}+\dfrac{1}{24}=\dfrac{7}{30}}$ đáp án D
Xem thêm các bài tiếp theo bên dưới